Building Early Numeracy Skills: A Literature Review of Numeracy Learning Implementation in Early Childhood - Siti Anastasya Putri; Hapidin; Sri Wulan (Didaktika: Jurnal Kependidikan, 2026)
Numeracy skills are basic skills that are important to be developed from an early age because they play a role in forming logical thinking skills, problem solving, and children's learning readiness at the next level of education. Numeracy learning in early childhood education needs to be implemented in accordance with the characteristics of child development and learning principles in the PAUD curriculum. This study aims to systematically examine the implementation of numeracy learning in early childhood through a literature review and analyze its suitability with the perspective of the PAUD curriculum and learning principles in the Independent Curriculum. The method used is a literature study by analyzing ten relevant national journal articles, obtained through Google Scholar databases, GARUDA, and university journal portals. The selected articles were analyzed based on the focus of numeracy learning implementation, research subjects, and main findings. The results of the study show that the implementation of numeracy learning in early childhood is generally carried out through a play approach, the use of concrete and game-based media, habituation of daily activities, and child-centered learning strategies. In addition, the role of teachers and a numeracy-rich learning environment are important factors in learning success. The findings of the study also show that the practice of numeracy learning is generally in line with the principles of the PAUD curriculum and the Independent Curriculum, although there are still limitations in planning and consistency of implementation in the field. This research is expected to make a theoretical and practical contribution to the development of early childhood numeracy learning as a foundation for improving the quality of education towards a Golden Indonesia 2045.